Red swamp crayfish: biology, ecology and invasion - an overview - Loureiro,Tainã Gonçalves (2015)
ABSTRACTAlien species have been transported and traded by humans for many centuries. However, with the era of globalization, biological invasions have reached notable magnitudes. Currently, introduction of alien species is one of the major threats to biodiversity and ecosystem functioning. The North American crayfish Procambarus clarkii is one of the most widely introduced freshwater species in the world, especially due to its high economic importance. It is responsible for great modifications in invaded environments causing irreparable ecological and economic damages. Its impressive ability to successfully colonize a wide range of environments is a consequence of its behavioural and biological characteristics that can adapt to features of the invaded location, conferring to this species a notable ecological plasticity. This review summarizes the available information regarding P. clarkii's biology and invasive dynamics around the world in order to contribute to the understanding of the threats posed by its establishment, as well as to support management and impact mitigation efforts.